Contemporary problems connected with including Standard for the Exchange of Product Model Data (ISO 10303 - STEP) in designing ontology using UML and XML - Skarka, Wojciech (Computer Assisted Methods in Engineering and Science; Vol 12 No 2-3 (2005), 2022)
Standard for the Exchange of Product Model Data (STEP-ISO 10303) contains product information models covering most of the aspects of product lifecycle management (PLM). In designing ontology of knowledge base concerning any aspects of PLM it is necessary to use such product information models. Unfortunately, a model based on STEP is based on EXPRESS language which is not compatible with common technologies for ontology creation. The paper presents contemporary methods of ontology description and it describes the importance as well as current level of advancement in development of STEP standard. Attention has been paid to drawbacks in possibilities of already existing methods, included in STEP for ontology creation, which could form a foundation for knowledge base designing methodology founded on the defined ontologies. A method of ontology creation has been proposed, including STEP model and examples of this method application in knowledge base implementation have been given.